Oral Sensory Sensitivity Influences Attentional Bias to Food Logo Images in Children: A Preliminary Investigation - Wallisch, Anna; Little, Lauren M.; Bruce, Amanda S.; Salley, Brenda (Frontiers in Psychology, 2022)
Background. Children’s sensory processing patterns are linked with their eating habits; children with increased sensory sensitivity are often picky eaters. Research suggests that children’s eating habits are also partially influenced by attention to food and beverage advertising. However, the extent to which sensory processing influences children’s attention to food cues remains unknown. Therefore, we examined the attentional bias patterns to food versus nonfood logos among children 4-12 years with and without increased oral sensory sensitivity. Design. Children were categorized into high (n=8) versus typical (n=36) oral sensory sensitivity by the Sensory Profile-2 (Dunn, 2014). We used eye-tracking to examine orientation and attentional bias to food versus nonfood logos among children with high versus typical oral sensory sensitivity. We used a mixed model regression to test the influence of oral sensory sensitivity to attentional biases to food versus nonfood logos among children. Results. Results showed that children with high oral sensory sensitivity showed attentional biases toward nonfood logos; specifically, children with high oral sensory sensitivity oriented more quickly to nonfood logos as compared to food logos (p<.05), as well as spent more time looking at nonfood logos as compared to food logos (p<.05). Findings were in the opposite direction for children with typical oral sensory sensitivity. Conclusions. Sensory sensitivity may be an individual characteristic that serves as a protective mechanism against susceptibility to food and beverage advertising in young children.